The development prototype model of instrument support table for Infusion pump on ambulance stretchers - ภูศรี ภูริพัฒน์; โพธิ์หลวง วิทยา (Thammasat University Hospital Journal Online, 2022)
Thammasat University Hospital simultaneously provides an emergency medical service and interfacility patient transfer for approximately 60 to 100 patients with critical conditions per month. Likewise, most of these patients require high alert drugs that are closely monitor and given via infusion pumps, syringe pumps and hemodynamic monitoring equipment. According to the clinical practice analyses, referral teams have faced with a limited space to place medical devices and struggle with mobile intravenous stand loading an extensive heavy medical equipment. It causes difficulty and inadequate monitoring during patient transfer that may lead to patient risks. Thammasat University Hospital - instrument support table was developed based on concept of adjustable and suitable for all ambulance stretcher types. It is an intervention that can help to provide more space and place for administrating infusion pumps and medical devices during patient transfers. This table can carry up to 5 infusion pumps and 8 intravenous fluid bags. TUH-instrument support table were used in over 30 clinical simulation situations with a feasibility outcome. Concurrently, there was no equipment falling or any tool dysfunction incidence. To disseminate the innovative table, TUH-instrument support table was tested and performed to apply with ambulance stretchers across emergency medical services at Thammasat University hospital for improving interfacility patient transfers and enhancing patient safety.